(untitled) (Memorias Sifored - Encuentros Educación UAN, 2021)
Understand and experience the corporeity in Colombian children and adolescents with obesity or pre-diabetes through artistic practices as a possibility of reflective and observable action in the incorporation of healthy bodily habits.